Systemic Inflammation and Early Pregnancy Loss: Evaluating Platelet-to-Albumin Ratio in First Trimester Threatened Abortion - Okutucu, Gülcan; İpek, Göksun and Şahin, Dilek (Cerrahpaşa Medical Journal, 2025)
Objective: To evaluate the clinical significance of the platelet-to-albumin ratio (PAR) as a predictive marker for early pregnancy loss (EPL) and adverse perinatal outcomes in first-trimester pregnancies complicated by threatened abortion (TA). Methods: This retrospective case-control study included 60 pregnant women hospitalized for TA and 60 matched healthy controls with term pregnancies, evaluated at Ankara Bilkent City Hospital Hospital between September 2024 and March 2025. First-trimester laboratory parameters, including PAR (calculated as platelet count divided by albumin level), were compared between groups. Demographic data, pregnancy outcomes, and perinatal complications were also analyzed. Receiver operating characteristic (ROC) analysis was performed to assess the predictive value of PAR for EPL. Results: The PAR was significantly lower in the TA group (5.15 ± 1.45) compared to controls (P < .001). Early pregnancy loss occurred in 30% of the TA cases, with a median diagnosis at 8 weeks’ gestation. The PAR cut-off value of 4.96 predicted EPL with 66.7% sensitivity and 67.7% specificity (area under the curve = 0.697, P = .008). Patients with TA also had significantly higher white blood cell counts and adverse perinatal outcomes, including lower birth weights, higher neonatal intensive care unit admissions, and increased C-section rates. Subgroup analysis based on gestational age at TA diagnosis revealed elevated inflammation markers in later first-trimester cases but no significant differences in EPL rates. Conclusion: Lower PAR values are associated with TA and may serve as a cost-effective, accessible marker to predict EPL and adverse perinatal outcomes. Although its predictive capacity is moderate, PAR could aid in early risk assessment when combined with other clinical parameters. Further large-scale, prospective studies are needed to validate these findings and establish PAR’s role in obstetric care. Cite this article as: Okutucu G, İpek G, Şahin D. Systemic inflammation and early pregnancy loss: evaluating platelet-to-albumin ratio (PAR) in first trimester threatened abortion. Cerrahpaşa Med J. 2025, 49, 0055, doi:10.5152/cjm.2025.25055.